Pouteria sapota (Red Mamey Fruit): Chemistry and Biological Activity of Carotenoids - Lakey-Beitia, Johant; Vasquez, Velmarini; Mojica-Flores, Randy; Fuentes C., Arelys L.; Murillo, Enrique; Hegde, Muralidhar L.; Rao, K.S. (Combinatorial Chemistry & High Throughput Screening, 2022)
Background: Red mamey is the fruit of P. sapota, a tree found in Mesoamerica and Asia. This fruit is considered a nutraceutical due to its multiple beneficial health including antiamyloidogenic activity and potential anti-tumorigenic property. Red mamey contain a variety of carotenoids including novel ketocarotenoids such as sapotexanthin and cryptocapsin. A ketocarotenoid is a chemical compound with a carbonyl group present in the β-ring or in the double bond chain of a carotenoid. In red mamey, the 3'-deoxy-k-end group in sapotexanthin has proven to be an important pro-vitamin A source, which is essential for maintaining a healthy vision and cognitive processes. Objective: This work reviews the current knowledge about the chemistry and biological activities of carotenoids in red mamey. Method: An exhaustive extraction is the most usual methodology to isolate and thoroughly characterize the carotenoids present in this fruit. High performance liquid chromatography is used to determine the profile of total carotenoids and its purity, while atmospheric pressure chemical ionization was used to determine their molecular weight and nuclear magnetic resonance determined their structure. Result: For each 100 g of fresh weight, 0.12 mg of total carotenoid from this fruit can be obtained. Out of the more than 47 reported carotenoids in red mamey, only 34 have a detailed characterization. Conclusion: It is important to continue studying the chemical composition and biological activity of this unique tropical fruit with commercial and nutritional value.
Keywords: Red mamey